Sythesis, electrochemistry, phase studies and computational chemistry of gamma-substituted betadiketonato-carbonyl complexes of rhodium(I) - Stuurman-Molefe, Nomampondomise Faurette (University of the Free State, 2014)
Synthetic routes to prepare β-substituted and γ-substituted β-diketones, rhodium(I)dicarbonyl and rhodium(I)monocarbonyltriphosphine complexes were developed and optimised, All complexes were characterised with 1H NMR, 31P NMR, and IR. Further characterisation of the complexes was done by means of the electrochemical techniques, DSC and POM. Cyclic voltammetry of the studied complexes shows irreversable chemical and electrochemical behaviour for both the reduction of the ligands and the oxidation of Rh(I). DFT calculations were used to optimise the neutral, the reduced, doubly reduced and triply reduced β-diketones, as applicable. Phase study of the synthesized compounds was done by means of a differential scanning calorimeter and a polarizing optical microscope. It was found that β-diketones exhibit different liquid crystalline mesophases before melting to an isotropic liquid. Rhodium(I)dicarbonyl complexes exhibit clear crystalline solid and isotropic liquid phase, while [Rh(β-diketonato)(CO)(PPh3)] has no crystal packing.

Sintetiese roetes vir β- en γ-gesubstieerde β-diketone, rodium(I)dikarboniel en rodium(I)monokarbonieltrifosfien komplekse was ontwikkel en geoptimaliseer. Alle komplekse is deur middel van 1H NMR, 31P NMR, en IR gekarakteriseer. Verdere karakterisering van die komplekse is deur middel van elektrochemiese tegnieke, DSC en POM gedoen. Sikliese voltammetrie van die bestudeerde komplekse toon chemiese en elektrochemiese onomkeerbare prosesse vir beide die reduksie van die ligand en die oksidasie van Rh(I). DFT berekeninge is gebruik om, waar van toepassing, die neutrale, die gereduseerde, die dubbel gereduseerde en die trippel gereduseerde β-diketone te optimiseer. 'n Fasestudie van die gesintetiseerde komplekse is gedoen met behulp van 'n DSC ("differential scanning calorimeter") en 'n POM (polariserings optiese mikroskoop). Dit is gevind dat β-diketone verskillende kristallyne meso-fases toon voordat dit in 'n isotropiese vloeistof in smelt. Rodium(I)dikarboniel komplekse toon duidelike kristallyn vaste- en isotropiese vloeistof fases, terwyl [Rh(β-diketonato)(CO)(PPh3)] geen kristalpakking toon nie.
Thesis (Ph.D. (Chemistry))--University of the Free State, 2014
Keywords: β-diketones; β-substituted; γ-substituded; Rhodium(I)dicarbonyl; Rhodium(I)monocarbonyltriphosphine; DFT; Cyclic voltammetry; DSC Phase study